Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Modulus proof

  1. Jun 29, 2008 #1
    hi all,
    i was studying modulus when i came across this mod(xy) = modx mod y
    we consider 3 cases
    whereby both positive , both negative, or positive negative

    it reads here if we consider x and y to be negative
    it will be something like this

    mod xy = xy = - mod x ( - mod y ) = mod x mod y
    therefore proven

    i do not understand why it is -mod x and -mod y
    i know that it says that x and y has to be negative
    but isnt -mod x different from mod x ? eg if x is 2 , -mod x will be -2 , and mod x will be 2
    correct me if i'm wrong
    i'm lost
  2. jcsd
  3. Jun 29, 2008 #2

    matt grime

    User Avatar
    Science Advisor
    Homework Helper

    If x is negative, then mod(x)=-x. So what you've got there is that we've noted

    x = -(-x)
    y = -(-y)


    xy = (-(-x))(-(-y)) = (-mod x)(=mod y)

    if x,y <0.

    And, yes mod(x) and -mod(x) are obviously different, so you're correct there.
  4. Jun 30, 2008 #3
    hey matt ,
    but according to the proof
    it's mod xy = xy = - mod x ( - mod y ) = mod x mod y

    why can't it be
    mod xy = xy = mod x mod y
    why does it have to have an additional -mod x (-mod y) ?
  5. Jun 30, 2008 #4
    Because both x and y are negative and not equal to mod x or mod y respectively, but to -mod x and -mod y.
  6. Jun 30, 2008 #5

    matt grime

    User Avatar
    Science Advisor
    Homework Helper

    Those equalities many (and indeed do) hold, but you want to *prove* that they do. So you have to use the *definition* of modulus for -ve numbers, rather than just writing what you want to be true, i.e. go the extra mile and make things explicit.

    Think of it this way: you know that mod(x)=-x if x<0, now you want to show, using this knowledge, that if x,y<0, then mod(xy)=mod(x)mod(y).

    Since x and y are less than 0, xy>0, so mod(xy)=xy.

    Now, mod(x)=-x and mod(y)=-y, thus mod(x)mod(y)=(-x)(-y)=xy, so all is fine.

    All the proof does is put those things together in one line.
  7. Jun 30, 2008 #6


    User Avatar
    Staff Emeritus
    Science Advisor

    What definition of "modulus" are you using?. It seems to me that to prove something that fundamental you would want to use the precise definition.
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?

Similar Discussions: Modulus proof
  1. Multiplicative modulus (Replies: 1)

  2. Modulus and inequalities (Replies: 14)

  3. Modulus integration (Replies: 9)

  4. Modulus of a tensor (Replies: 1)